Carbapenem-Only Combination Therapy against Multi-Drug Resistant Pseudomonas aeruginosa: Assessment of In Vitro and In Vivo Efficacy and Mode of Action - Brendan Mackay; Benjamin J. Parcell; Sally L. Shirran; Peter J. Coote (MDPI AG, 2022)
The aim of the study was to determine the efficacy of carbapenem-only combination treatments derived from four approved drugs (meropenem, doripenem, ertapenem and imipenem) against a MDR strain of P. aeruginosa in a Galleria mellonella larvae infection model. G. mellonella larvae were infected with P. aeruginosa NCTC 13437 (carrying the VIM 10 carbapenamase) and the efficacy of the six possible dual, four triple, and one quadruple carbapenem combination(s) were compared to their constituent monotherapies. Four of these combinations showed significantly enhanced survival compared to monotherapies and reduced the bacterial burden inside infected larvae but without complete elimination. Bacteria that survived combination therapy were slower growing, less virulent but with unchanged carbapenem MICs-observations that are consistent with a persister phenotype. In vitro time-kill assays confirmed that the combinations were bactericidal and confirmed that a low number of bacteria survived exposure. Mass spectrometry was used to quantify changes in the concentration of carbapenems in the presence of carbapenemase-carrying P. aeruginosa. The rate of degradation of individual carbapenems was altered, and often significantly reduced, when the drugs were in combinations compared with the drugs alone. These differences may account for the enhanced inhibitory effects of the combinations against carbapenem-resistant P. aeruginosa and are consistent with a 'shielding' hypothesis. In conclusion, carbapenem combinations show promise in combating MDR P. aeruginosa and are worthy of additional study and development.